Data structures, algorithms, and object-oriented programming - Heileman, Gregory L. (McGraw-Hill, 1996)
The book provides a modern treatment of data structures and rigorous analyses of their corresponding algorithms. Implementation of these data structures is considered from the perspective of object-oriented programming, and is supported by detailed examples in C++